Konstribusi Tafsir Kontemporer dalam Menjawab Persoalan Ummat (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2013)
Interpretation is a means to explain the holy message of the Koran to be  widely understood by many and practiced in real life. Interpretation of the Qur’an  has been going on for a long time, starting from the time he was demoted to the  present and even the future. The Qur’an is also a scripture that applies to all  Muslims wherever and whenever it is. Efforts to interpret the Qur’an in the  present or the better known contemporary interpretation has a very strategic role  in the realm of Islamic scholarship. The development of information technology  has brought such tremendous influence on the lifestyle of modern society. It also  contributes to the development raises new issues in the various dimensions of life.  The issue is so complex and the solution certainly needed a way out so that the  Muslim community in particular human life running harmoniously. Interpretation  of the Qur’an is done by experts in the contemporary era has been a lot of  investigating and talking about a variety of issues. This short article will discuss  about the contribution of the interpretation of contemporary in an effort to provide  solutions to the various problems of the ummah
Keywords: Corak Tafsir; Kontemporer; Ummat